The Study of Multidrug Resistance Escherichia Coli in Drinking Water Samples from 9th District of Kabul City - Ataye, Ahmad Wali; Ehsan, Ehsanullah; Razavi, Farida; Kohistani, Abdul Moaid; Ebrahimi, Qudratullah; Mandezai, Noorullah (Eximia, 2022)
Antibiotic resistance in pathogenic Bacteria is a serious public health issue. Various factors contribute to the spread of antibiotic –resistance microorganisms in the environment. This study was aimed for detection of multi drug resistance Escherichia Coli in drinking water samples from 9th district of Kabul city..Water sample is taken in Simple Random Sampling. The population size of drinking water sampling is N=378 and by using of Epi – info program, the water sample is selected and so, the sample size of water sample is 378 samples, therefore 126 water sample from house hold ,126 samples from supplies and 126 samples from collection tankers of 9th district of Kabul city. Samples of drinking water from district 9th of Kabul city were collected in a sterile bottle from various parts of district 9th of Kabul city bringing into Microbiology Department and growing it in mac-conkey agar. the collected data is by using of MS –excel and SPSS software was analyzed. out of 378 samples collected in 243 (64.3%) Escherichia coli were isolated and 135(35.7%) samples were free of E.coli. Maximum resistance was observed against Nalidixic acid( 64.3%) followed by ampicilline) 59.5%),Ciprofloxacine,( 57.1%.It is also remarkable that percentage of Escherichia coli in different sources of 9th district of Kabul city such as house hold, supplies and collection tanker was as follows: 27.1%,30.8% and 41.9%%. In conclusion this study found that contaminated percentage of drinking water in 9th district of Kabul city was higher 64.3% and presence of E-coli is higher in tanker collection and antibiotic resistance is higher against Nalidixic acid .Further studies is needed for better results in future.